A new combination in Qualea subg. Amphilochia (Vochysiaceae) from Brazilian Cerrado - Sampaio, Thiago Henrique Silva; Teles, Aristônio Magalhães (Phytotaxa, 2017)
The Cerrado domain is located almost exclusively in the Central Plateau of Brazil and covers some 2 million km2 (Ratter et al. 1997), and is also considered one of the 25 most important terrestrial hotspots of the world due to the high diversity and endemism (Myers et al. 2000, Marinho-Filho et al. 2002, Mittermeier et al. 2004, Carmignotto et al. 2012). Among the most important plant families in terms of species abundance in Cerrado, Vochysiaceae stands out as characterizer element of the domain, and by the bioaccumulation of aluminum (Haridasan 1982, Haridasan & Araújo 1998).